A puzzle to be named later [large type] : a Puzzle Lady mystery - Hall, Parnell (Hall, Parnell. Puzzle Lady mystery., 2017)
"The Puzzle Lady couldn't be happier. Matt Greystone, the rookie sensation who just signed a huge contract with the Yankees after coming to the team as the player to be named later in a trade with the Diamondbacks, winning 17 games as a starting pitcher, was coming to town to rehab from an arm injury. A diehard Yankee fan, Cora was delighted when Matt invited her to a weekend pool party. On the plus side, she got to meet Derek Jeter. On the minus side, she had to solve a puzzle (that was also named later) and a couple of the guests got killed"--Provided by publisher.